Factors Contributing to Active Aging in Older Adults, from the Framework of Roy’s Adaptation Model - Salazar-Barajas, Martha Elba; Lillo Crespo, Manuel; Hernández Cortez, Perla Lizeth; Villarreal Reyna, María de los Ángeles; Gallegos Cabriales, Esther Carlota; Gómez Meza, Marco Vinicio; Salazar Gonzalez, Bertha Cecilia (Investigación y Educación en Enfermería, 2018)
Objective. To determine the variables contributing to the explanation of active aging according to Roy’s adaptation model. Methods. Descriptive correlational study, with convenience and snowball sampling. Two hundred older adults with chronic disease, were included. The instruments used were: a) Yesavage’s Geriatric depression scale, b) Pheiffer’s mental state questionnaire, c) basic activities of daily living, d) instrumental activities of daily living, e) Hope scale, f) coping mechanism items from the Successful Aging Inventory (coping with aging), g) hours of volunteer work, and h) The Duke-UNC Functional Social Support Questionnaire. Coping with aging was composed of independence in basic and instrumental activities of daily living, free from symptoms of depression, good mental state, and perception of health as good. Data were analyzed by using descriptive and inferential statistics, and simple and multiple linear regression models. Results. Fifty one percent of the participants showed active aging (42% men, and 56% women). Of the proposed variables, the variables showing effect on the variables of active aging, in the generalized linear model, were years of suffering the disease (Λ=0.922; p=0.008), coping with aging (Λ=0.582; p=0.001), and perceived social support (Λ=0.885; p=0.001). These three variables explained 5% of basic activities of daily living, 41% of the instrumental activities, 12.5% of health perception, 26% of mental state, and 21% of depression. Hope, and volunteer work were not significant. When the variables of active aging were dichotomized, age showed negative effect on global active aging and coping with aging positive effect. Conclusion. Although, proposed variables explained individually active aging, only coping with aging explained global active aging. How to cite this article: Salazar-Barajas ME, Lillo CM, Hernandez CPL, Villarreal RMA,Gallegos CE, Gómez MM, Salazar – Gonzalez BC. Factors Contributing to Active Aging in Older Adults, from the Framework of Roy’s Adaptation Model. Invest. Educ. Enferm. 2018; 36(2):e08.